Upstream and downstream revenue of upper gastrointestinal endoscopic ultrasound determined with an episode-of-care approach - Maeng, Daniel; Wall, Beth; Hassen, Dina; Diehl, David L. (Endoscopy International Open, 2019)
Background and study aims Upper gastrointestinal endoscopic ultrasound (EUS) has clinical advantages that can lead to improved patient outcome. This study seeks to characterize and quantify the upstream and downstream healthcare utilizations and revenues.Patients and methods A retrospective claims data analysis of upper gastrointestinal EUS procedures was conducted at a large health system. Types of care and total revenues associated with each episode of care were characterized by descriptive statistics. Comparisons were made between patients who had Medicare Advantage and commercial plans as well as those with and without cancer diagnoses during the downstream period.Results A total of 436 cases were identified. The most frequent downstream healthcare utilizations consisted of radiology (31 %), pathology services (28 %), and high-revenue services including chemotherapy and inpatient admissions. The most common upstream utilizations included radiology (18 %) and lab services (22 %). Average total downstream revenue was $ 34 231 (95 %CI: $ 28 561 – $ 39 901) per case, and average total upstream revenue was $4373 (95 %CI: $3227 – $ 5519). Average total revenue per case did not differ significantly between Medicare Advantage and commercial plan members. However, patients who were diagnosed with cancer at or immediately following EUS (20 %) were associated with significantly higher total revenue compared to those without cancer diagnosis (P < 0.0001).Conclusions This episode-of-care approach to quantifying the revenue impact of upper gastrointestinal EUS to the providers suggests there are substantial downstream as well as upstream revenues associated with upper gastrointestinal EUS procedures, driven by patients who are diagnosed with cancer by the EUS procedures and subsequently require oncologic care.